Evaluation of population parameters and biometric data of an Eurasian Collared Dove (Streptopelia decaocto Friv.) population in the Great Plain of Hungary - Varga, Sámuel; Juhász, Lajos (Acta Agraria Debreceniensis, 2018)
The Eurasian Collared Dove shows different patterns in density all over Hungary. In some cases, the population has decreased to a lower level, but there are habitats where the population remained stable. Several factors were taken into consideration during the evaluation of this phenomenon. These publications state that the increased urbanization of corvids, the lack of food sources, and the changes in nesting sites caused the decrease in numbers. During our research, we intend to contrast the differences in population structure of Collared Doves that differ from each other in the density of predators presented at nesting sites. As a first step, in this paper, numerous samples (n=118) were taken from a population that is less influenced by corvid species’ nest predation. Our prediction was that the population parameters remained at the level of 1980’s, in which the population of Eurasian Collared Dove has reached its maximum, according to further publications. During the evaluation process, our data were collected from hunting bags near Nyíregyháza. Results were compared with former publications. We stated that the population structure, such as age and gender distribution remained stable in the evaluated population. In addition, morphometric factors of the collected individuals were also measured, such as weight, wing length, 3rd primary feather, and tail length, which were compared with former surveys. During statistical tests no significant difference was revealed among population parameters, but there were significant differences between most of the morphometric data, (p>0.05).